Probing the effects of redox conditions and dissolved Fe2+ on nanomagnetite stoichiometry by wet chemistry, XRD, XAS and XMCD. Issue 7 (18th June 2021) - Jungcharoen, Phoomipat; Pédrot, Mathieu; Choueikani, Fadi; Pasturel, Mathieu; Hanna, Khalil; Heberling, Frank; Tesfa, Marawit; Marsac, Rémi
Abstract : Magnetite oxidation and/or interaction with dissolved Fe(ii ) induce surface recrystallization processes, which can be probed by XMCD. Abstract : Magnetite nanoparticles, commonly found in subsurface environments, are extensively used in various applications such as environmental remediation, catalysis, electronics and medicine. However, the oxidative transformation of magnetite (mixed-valent Fe-oxide) into maghemite (Fe(iii )-oxide) that drastically affects magnetic, catalytic and redox properties of the mineral, is still poorly understood. In the present study, a thorough characterization of both particle core and surface of magnetite was performed to accurately assess the relationship between mineral composition and reactivity within the magnetite/maghemite core–shell structure. Previous work showed that X-ray absorption spectra (XAS) and X-ray magnetic circular dichroism (XMCD) can provide key insights into magnetite stoichiometry ( R = Fe(ii )/Fe(iii )) of 10 nm sized particles, as compared to wet chemistry and X-ray diffraction (XRD). In the present study, XMCD signals have been used to further characterize the complex reactions involved in the magnetite/maghemite system upon oxidation and recharge processes, e.g. decreasing R from 0.5 to 0.1 using H2 O2 or increasing from 0.1 to 0.5 through dissolved Fe 2+ amendment. Indeed, surface recrystallization processes, induced by oxidation as well as Fe 2+ diffusion into the solid phase and/or redistribution of electron equivalents between the aqueous solution and the magnetite bulk, led to decreased spin canting effects, altering XMCD signals. This study provides a fundamental understanding of the processes occurring in the magnetite/maghemite system upon the alteration of the redox conditions and offers a more accurate method for the determination of magnetite stoichiometry by XMCD.